Performance of cotton (Gossypium hirsutum L.) under aonla (Emblica officinalis Gaertn.) based multistoried agroforestry system in Terrace Ecosystem of Bangladesh - Mortuza, M.G.G.; Miah, M.G.; Miah, M.M.U.; Saha, S.R.; Rizvi, Javed (Indian Journal of Agroforestry, 2020)
The study was conducted in ten years old aonla orchard, which was considered as upper storey crop, while two minor fruits namely carambola and lemon were used as middle storey crop to learn about the growth, yield and yield contributing characters of cotton variety on multistoried agroforestry system in the terrace ecosystem of Bangladesh. Cotton varieties were used as lower storied crop. Three cotton varieties (V1 : CB 9, V2 : CB 10 and V3 : CB 11) were tested following Randomized Complete Block Design (RCBD) with three replications. Three different combinations were T1 : Aonla only, T2 : Aonla + Middle storied tree species (Carambola and Lemon), and T3 : Open Field (control). Among the cotton varieties (CB 9, CB 10 and CB 11) most of the yield and yield contributing characters i.e., sympodial branch, number of boll per plant, weight of single boll, and yield were influenced significantly by the combined effects of trees and varieties. The CB 10 produced the maximum number of sympodial branches per plant at all agroforestry systems and open field condition in both the cropping seasons. The longest duration was recorded in T2V1 and the shortest duration was found in T3V2. The maximum number of bolls per plant and seed cotton yield were observed in CB 10 variety at open field condition (T3V2) in the both cropping seasons, whereas, the minimum number of bolls per plant and the lowest seed cotton yield was recorded in T2V3 treatment in both the growing seasons. The highest GOT and the maximum PSI was found for cotton variety CB 10 at all agroforestry systems and open field condition in both the cropping seasons. Therefore, Cotton variety (CB 10) would be cultivated in aonla based multistoried agroforestry system for terrace ecosystem of Bangladesh to have better production and additional income.